Acceleration of Land Rights Certification Through Settlement of Land Tax Obligations - Sinaga, Roulinta Yesvery; Kuahaty, Sarah Selfina; Sihite, Sri Rumada; Dyastuti, Risqi Mumpuni (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The Complete Systematic Land Registration Program (SLRP) is a government effort to evenly accelerate the provision of land certificates to the Community. Although the certificate is given free of charge, participants are still obliged to pay Income Tax and Land and Building Acquisition fees (BAT). For participants who cannot pay, a mechanism is provided in the form of a tax debt statement. The challenges include minimal socialization, weak institutional coordination, and administrative obstacles. Therefore, there is a need to simplify procedures and more effective tax education.Purposes of the Research: This study aims to examine the problem of what obstacles are faced by the parties responsible for the settlement of income tax and for land rights applicants, namely building acquisition tax (BAT) in the complete systematic land registration program (SLRP), and analyze how to optimize the settlement of Income Tax and BAT to utilize the land certificates made optimally.Methods of the Research: The research method is an empirical legal method with a qualitative legal approach.Results Main Findings of the Research: The results of this study found obstacles in SLRP, namely the absence of clear and consistent regulations regarding the payment of Income Tax and BAT in the Central Maluku region, the need for increased communication between the Central Maluku Regency Land Office and the Central Maluku Regency Government, and the improvement of apparent socialization regarding Taxes to the Community. Meanwhile, several stages can be carried out to optimize land certificates regarding settlements related to income tax and BAT taxes. Namely, the initial step is to form a team to conduct data collection on applicants for rights that are still owed and to conduct socialization and coordination with other agencies, such as the authorities in collecting Income Tax and BAT taxes owed, to make efforts to jointly seek solutions in optimizing the complete systematic land registration program (SLRP).